Peritoneal Fluid Analysis of the Newborn Calves with Intestinal Atresia - a Clinical Approach - Salci, Hakan; Catik, Serkan; Ozdemir, Emsal Sinem; Ozakin, Cuneyt (Acta Scientiae Veterinariae, 2019)
Background: Anomalies and fetal problems are encountered in all animals. Intestinal atresia is a congenital anomaly of both humans and animals. Intestinal atresia has four morphological types, and they can be observed in jejunum, ileum, cecum, colon, rectum and anus (type I: mucosal atresia, type II: atretic ends separated by fibrous cord, type III: atretic ends separated by a “V” shaped mesenteric gap or atretic end coil like an “apple peel”, type IV: multiple atresia). In calves, it is also commonly encountered; it is still a question to be replied about the exact prognosis of the patients with intestinal atresia. Thus, the main objective of the present study was to evaluate peritoneal fluid analysis results of calves with intestinal atresia. Materials, Methods & Results: Twenty-two calves were presented with abdominal distension and lack of defecation. Clinical and radiological findings pointed out the intestinal atresia. Blood samples were collected for routine hematological and serum total protein (TP) analysis. Peritoneal fluids were aspirated with sterile technique from the caudal abdomen, and biochemical features, cell contents and microbiological cultures of the peritoneal fluids were analyzed. Following to preoperative, surgical and necropsy findings, intestinal atresia were diagnosed as type II, III and IV in calves. Neutrophilic leukocytosis was observed in calves with type IV intestinal atresia. Red blood cells and platelet counts were determined in the peritoneal fluids. TP and density values of the peritoneal fluid were high in all cases. These results pointed the presence of the acute infection and peritonitis. Statistical comparison of each parameter showed that there was no significant difference between the types of intestinal atresia. Microbiologically, fecal origin bacteria were cultured in 12 calves. Discussion: In general, four types of intestinal atresia are encountered in calves, and all types are fatal pathologies; thus, surgery should urgently be planned as soon as diagnostic work-ups are completed after birth. Peritoneal fluid analysis is a useful diagnostic choice because changes in the peritoneal fluid parameters help to diagnosis of the intra-abdominal pathology. Intestinal atresia as more common anomaly in Holstein, Jersey and Montafon breed calves. In animals with intestinal atresia, surgical treatment is not usually recommended due to economic reasons and small chance of postoperative success. Long-term survival rate of surgically treated animals depends on the type of intestinal atresia and applied surgical technique. Atresia recti and ani may occur simultaneously with atresia coli, and all atresias (atresia coli, ani, recti or ani et recti) can be successfully treated by surgery. Continuous distention of the large intestinal segments leads to ischemia, necrosis, peritonitis and bowel perforation. Peritoneal fluid analysis should include the classic parameters for diagnosis, but these analyses are often insufficient to identify the etiology or pathogenesis of the disease. An increase in total WBC count and percentage of the neutrophil cells in the peritoneal fluid indicate the acute infectious origin inflammation. Additional parameters in the peritoneal fluid analysis have been established to improve diagnostic precision and specific information. Presence or absence of the bacteria in the peritoneal fluid samples is important to characterize the transudate and exudate. Changings in the peritoneal fluid values does not related to type of the intestinal atresia in calves.